Sirtuins: Key players in obesity-associated adipose tissue remodeling - Chen, Jiali; Lou, Ruohan; Zhou, Fei; Li, Dan; Peng, Cheng; Lin, Ligen (Frontiers in Immunology, 2022)
Obesity, a complex disease involving an excessive amount of body fat and a major threat to public health all over the world, is the determining factor of the onset and development of metabolic disorders, including type 2 diabetes, cardiovascular diseases, and non-alcoholic fatty liver disease. Long-term overnutrition results in excessive expansion and dysfunction of adipose tissue, inflammatory responses and over-accumulation of extracellular matrix in adipose tissue, and ectopic lipid deposit in other organs, termed adipose tissue remodeling. The mammalian Sirtuins (SIRT1–7) are a family of conserved NAD+-dependent protein deacetylases. Mounting evidence has disclosed that Sirtuins and their prominent substrates participate in a variety of physiological and pathological processes, including cell cycle regulation, mitochondrial biogenesis and function, glucose and lipid metabolism, insulin action, inflammatory responses, and energy homeostasis. In this review, we provided up-to-date and comprehensive knowledge about the roles of Sirtuins in adipose tissue remodeling, focusing on the fate of adipocytes, lipid mobilization, adipose tissue inflammation and fibrosis, and browning of adipose tissue, and we summarized the clinical trials of Sirtuin activators and inhibitors in treating metabolic diseases, which might shed light on new therapeutic strategies for obesity and its associated metabolic diseases.